Why does the `lim_(x->0) sin(x)/x = 1`

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Another way to show that

`lim_(x->0) sinx/x = 1`

is by using the L'Hospital rule. According to this rule, 

`lim f(x)/g(x) = lim (f'(x))/(g'(x))` .

That is, the limit of the ratios of functions equals to the limit of the derivatives, if this limit exists.

In the case of sin(x) and...

Unlock
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial

Another way to show that

`lim_(x->0) sinx/x = 1`

is by using the L'Hospital rule. According to this rule, 

`lim f(x)/g(x) = lim (f'(x))/(g'(x))` .

That is, the limit of the ratios of functions equals to the limit of the derivatives, if this limit exists.

In the case of sin(x) and x, 

(sin(x))' = cos(x)

and (x)' = 1.

So, since cos(0) = 1,

 `lim_(x->0) sinx/x = lim_(x->0) cosx/1 = 1`

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

Why is `lim_(x->0)(sin(x))/x=1 ` ?

We will use the squeeze theorem. Consider a right triangle with one side of length 1, and the acute angle formed by this side and the hypotenuse with measure `theta ` .(See attachment.)

Draw a circle with radius 1 and center the vertex of the angle marked `theta ` .

(1) The area of the triangle is 1/2 base times height or `(1/2)(1)(tan(theta))=tan(theta)/2 `

(2) The area of the sector determined by the sides of the acute angle is ` 1/2 r^2 theta=theta/2 `

(3) If we drop a perpendicular from the point of intersection of the circular arc to the side of length 1, and form a triangle using the points of intersection of the arc and the sides of the original right triangle we find that the area of this smaller triangle is ` (1/2)(1)(sin(theta))=sin(theta)/2 `

Now from the geometry we have:

`tan(theta)/2 >= theta/2 >= sin(theta)/2 `   Multiply through by ` 2/sin(theta) ` to get:

`1/cos(theta)>= sin(theta)/theta >= 1 ` or

`cos(theta)<=sin(theta)/theta <= 1 `

Note that `cos(-theta)=cos(theta) ` and `sin(-theta)/(-theta)=sin(theta)/theta ` , so the inequality holds for all nonzero `theta in ` `(-pi/2,pi/2) ` .

Now `lim_(x->0)cos(theta)=lim_(x->0)1=1 ` , so by the squeeze theorem `lim_(x->0)sin(theta)/theta=1 `

Images:
This image has been Flagged as inappropriate Click to unflag
Image (1 of 1)
Approved by eNotes Editorial Team